Plk is a functional homolog of Saccharomyces cerevisiae Cdc5, and elevated Plk activity induces multiple septation structures. - Lee, K S (1997)
Plk is a mammalian serine/threonine protein kinase whose activity peaks at the onset of M phase. It is closely related to other mammalian kinases, Snk, Fnk, and Prk, as well as to Xenopus laevis Plx1, Drosophila melanogaster polo, Schizosaccharomyces pombe Plo1, and Saccharomyces cerevisiae Cdc5. The M phase of the cell cycle is a highly coordinated process which insures the equipartition of genetic and cellular materials during cell division. To enable understanding of the function of Plk during M phase progression, various Plk mutants were generated and expressed in Sf9 cells and budding yeast. In vitro kinase assays with Plk immunoprecipitates prepared from Sf9 cells indicate that Glu206 and Thr210 play equally important roles for Plk activity and that replacement of Thr210 with a negatively charged residue elevates Plk specific activity. Ectopic expression of wild-type Plk (Plk WT) complements the cell division defect associated with the cdc5-1 mutation in S. cerevisiae. The degree of complementation correlates closely with the Plk activity measured in vitro, as it is enhanced by a mutationally activated Plk, T210D, but is not observed with the inactive forms K82M, D194N, and D194R. In a CDC5 wild-type background, expression of Plk WT or T210D, but not of inactive forms, induced a sharp accumulation of cells in G1. Consistent with elevated Plk activity, this phenomenon was enhanced by the C-terminally deleted forms WT deltaC and T210D deltaC. Expression of T210D also induced a class of cells with unusually elongated buds which developed multiple septal structures. This was not observed with the C-terminally deleted form T210D deltaC, however. It appears that the C terminus of Plk is not required for the observed cell cycle influence but may be important for polarized cell growth and septal structure formation.